2009
DOI: 10.1159/000218520
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Subjective Experience and Psychosis Risk in Young Depressed Patients

Abstract: Background: Help-seeking young people often display depressive symptoms. In some patients, these symptoms may co-exist with clinically high-risk mental states for psychosis. The aim of this study was to determine differences in subjective experience and social perception in young depressed patients with and without psychosis risk. Methods: Participants were 68 young persons with major depressive disorder. Twenty-six patients also met the criteria of attenuated or brief limited intermittent psychotic symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…The combined effect size for ToM (k = 8) was medium (g = −0.425, (Couture et al, 2008;Szily & Kéri, 2009). After these studies were eliminated, the combined effect size for ToM (k = 6) remained medium, and no significant heterogeneity was identified (I 2 = 0, g = −0.409, 95% CI = −0.584 to −0.234, p b 0.001).…”
Section: Effect Sizes and Meta-analytic Resultsmentioning
confidence: 98%
“…The combined effect size for ToM (k = 8) was medium (g = −0.425, (Couture et al, 2008;Szily & Kéri, 2009). After these studies were eliminated, the combined effect size for ToM (k = 6) remained medium, and no significant heterogeneity was identified (I 2 = 0, g = −0.409, 95% CI = −0.584 to −0.234, p b 0.001).…”
Section: Effect Sizes and Meta-analytic Resultsmentioning
confidence: 98%
“…Almost all studies employed the Reading the Mind in the Eyes assessment task ( 46 ), which required participants to interpret the affective mental state portrayed in various cropped images of eyes. The clear majority of studies found that depressed patients were impaired in this skill compared to controls ( 8 , 21 , 27 , 29 , 32 ). However, a separate study found depressed patients to be in fact more accurate than matched controls in identifying a negative emotional state, without any difference for neutral and positive states ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the use of the RMET, depressed young adults without psychosis risk were found to be able to recognize less negative social emotions (such as looking hostile), whereas depressed young adults with psychosis risk were found to be impaired on the recognition of both negative social emotions and cognitive expressions (inner thought states such as looking pensive) compared to controls [66]. Psychosis risk was assessed with the Comprehensive Assessment of at Risk Mental States (CAARMS) instrument [67].…”
Section: Resultsmentioning
confidence: 99%